Environmental effectiveness of GAEC cross-compliance Standard 1.1a (temporary ditches) and 1.2g (permanent grass cover of set-aside) in reducing soil erosion and economic evaluation of the competitiveness gap for farmers - Bazzoffi, Paolo; Francaviglia, Rosa; Neri, Ulderico; Napoli, Rosario; Marchetti, Alessandro; Falcucci, Margherita; Pennelli, Bruno; Simonetti, Giampiero; Barchetti, Antonio; Migliore, Melania; Fedrizzi, Marco; Guerrieri, Mirko; et al. (Italian Journal of Agronomy, 2016)
This paper shows the results of the monitoring carried out in three hilly farms of the MONACO project in order to verify the effectiveness of the Standard 1.1 (commitment a) (temporary ditches) and Standard 1.2 (commitment g) (Vegetation cover throughout the year in set-aside land) in the reduction in soil erosion, contained in Rule 1: ‘minimum land management that meets specific conditions’ of the decree Mipaaf 2009 and following modifications, until the recent decree No. 180 of January 23, 2015. In addition, the assessment of the competitiveness gap was done. That is the evaluation of the additional costs borne by the beneficiary of the single payment determined from agronomic commitments. Monitoring has also compared the erosion actually observed in the field with that predicted by RUSLE model (Revised Universal Soil Loss Equation) (Renard et al., 1997) in the two situations: with and without the presence of temporary ditches, i.e. assuming Factual (compliance rules) and in that Counterfactual (infringement). This comparison was made in view of the fact that the RUSLE model was chosen by the 'European Evaluation Network for Rural Development (EEN, 2013) as a forecasting tool for the quantification of' Common Indicator ‘soil erosion by water’. The results of soil erosion survey carried out by using a new UAV-GIS methodology on two monitoring farms in two years of observations have shown that temporary ditches were effective in decreasing erosion, on average, by 42.5%, from 36. 59 t ha-1 to 21.05 t ha-1 during the monitoring period. It was also evaluated the effectiveness of grass strips (at variance with the commitment of temporary ditches). The results showed a strong, highly significant, reduction in erosion by about 35% times respect soil erosion observed in bare soil and also a significant reduction in the volume of runoff water. With regard to Standard 1.2 (commitment g) the statistical analysis shows a strong and highly significant decrease in the erosion due to the vegetation cover of the soil compared to bare soil. The economic competitiveness gap of Standard 1.1(commitment a) stood at € 4.07±1.42 € ha-1 year-1, while CO2 emissions due to execution of temporary ditches was 2.58 kg ha-1year-1. As for the Standard 1.2 (commitment g) the average differential competitiveness gap amounted to 50.22±13.7 € ha-1 year-1 and an output of CO2 equal to 31.52 kg ha-1 year.